On Symbols In Films - Đoàn, Tiến Lực (Hanoi academy of theatre and cinema, 2021)
The language of cinema is a combination of different forms of expressions. According to Yuri Lotman, " Any unit of document can become an element in the language of cinema, as long as gives us a choice, and hence, it exists in the document not randomly, but with a specific meaning"